2011
DOI: 10.1016/j.expneurol.2011.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Niaspan enhances vascular remodeling after stroke in type 1 diabetic rats

Abstract: We investigated the changes and the molecular mechanisms of cerebral vascular damage and tested the therapeutic effects of Niaspan in type-1 streptozotocin induced diabetic (T1DM) rats after stroke. T1DM-rats were subjected to transient middle cerebral artery occlusion (MCAo) and treated without or with Niaspan. Non-streptozotocin rats (WT) were also subjected to MCAo. Functional outcome, blood–brain-barrier (BBB) leakage, brain hemorrhage, immunostaining, and rat brain microvascular endothelial cell (RBEC) cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 50 publications
4
48
2
Order By: Relevance
“…The release of Ex-4 from degradable PEx-4 then activated GLP-1R in the brain, leading to the effects on the brain cerebral blood flow intensity and microcirculation. Under DM and stroke insults, BBB endothelial leakage was enhanced, 32,33 possibly resulting in more PEx-4 microspheres and fragments entry into the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…The release of Ex-4 from degradable PEx-4 then activated GLP-1R in the brain, leading to the effects on the brain cerebral blood flow intensity and microcirculation. Under DM and stroke insults, BBB endothelial leakage was enhanced, 32,33 possibly resulting in more PEx-4 microspheres and fragments entry into the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting study showed that angiogenesis is impaired in the GK diabetic model after stroke and this is associated with decreased VEGF and increased angiostatin signaling. 112 In other studies where immature vessel formation was observed, 104,105 authors reported increased Ang-2 and decreased Ang-1 expression in the brain sections of diabetic rats. 103,104 V. Clinical Relevance On the basis of experimental evidence, cerebral neovascularization response differs in diabetes, stroke, and diabetic stroke ( Figure 6).…”
Section: Cerebral Neovascularization In Diabetes a Ergul Et Almentioning
confidence: 90%
“…Other studies also showed that type 1 and type 2 diabetes impair angiogenesis after stroke. 104,105 Vessel density in the ipsilateral hemisphere 14 days after stroke is increased but these vessels are not mature as indicated by reduced diameter, arteriolar density, and SMCs. 104,105 These studies were conducted in stroked animals and there were no sham control animals thus it is not possible to comment on how stroke injury affected the neovascularization response in the nonischemic hemisphere.…”
Section: Neovascularization After Stroke In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug selectively kills insulin-producing cells in the pancreas, rendering mice hyperglycemic and leading to sequelae that mimic T1D (7). STZ-treated mice with chronic elevations in blood glucose levels (;2-4 weeks) show greater neurological deficits and are less likely to regain full use and dexterity of the stroke-affected limbs after focal ischemic or embolic stroke (8)(9)(10). One caveat with this finding is that it occurs after persistent hyperglycemia rather than after chronic low-grade dysregulation of glucose levels that would typically be present in human patients with diabetes.…”
Section: Impaired Stroke Recovery In Rodent Models Of Diabetesmentioning
confidence: 99%